(untitled) (Global Journal of Human-Social Science, 2012)
This piece of writing on the theme Truth is a exercise based on philosophical social science and literary material The truth with different names— existence reality fact facticity attracted the attention of galaxy of established authors across disciplines The status of truth has been attempted here discussing epistemological linguistic critical constructivist poststructuralist and postmodernist perspectives It may be concluded that the concept of truth has still remained present in old and new volumes equally but has lost its prominent position in theory and logical discussions The concept moved from unifying and universal agreement to the disarrayed concept- either denial of its essentialist core and designated post modernist anti - essentialist relativism in later year theorist The debate now concentrates not on truth as such but on about truth And the hype-real simulations of the real presents before us many versions of truth detached from its existential truth at a higher order